The relationship between employees’ performance and working environment at Perbadanan Kemajuan Negeri Melaka, Melaka / Nur Farah Ain Zulkifli - Zulkifli, Nur Farah Ain (Faculty of Business and Management, 2019)
This study intends to investigate the relationship between employees’ performance and working environment. Four objective have been determined in order to achieved the purpose of the study. First, to identify the relationship between training and employees’ performance. Second, To determine the relationship between reward and employees’ performance. Third, to examine the relationship between work-life balance and employees’ performance. fourth, to investigate which factor most influence employees’ performance. The population of the study in Perbadanan Kemajuan Negeri Melaka(PKNM) consists of 360 employees and the sample size consists of 113 respondents. The data collected by distributing 130 questionnaire and 125 returned questionnaire and 113 questionnaire were used in the study. To analyse the data, descriptive, correlation and regression analysis was used